Seasonal Climate Manipulations Result in Species-Specific Changes in Leaf Nutrient Levels and Isotopic Composition in a Sub-Arctic Bog - Aerts, Rien; Callaghan, Terry V.; Dorrepaal, Ellen; van Logtestijn, Richard S. P.; Cornelissen, Johannes H. C. (Functional ecology, 2009)
1. Climate change in cold biomes not only involves higher summer temperatures, but also warmer springs and more winter precipitation. So far, little is known about species responses to these seasonal components of climate change. 2. We experimentally manipulated spring and summer temperatures and winter snow accumulation and temperatures independently in a peatland in sub-arctic Sweden. This yielded six climate scenarios and we studied the responses of the peat moss Sphagnum fuscum, the evergreen dwarf shrubs Empetrum hermaphroditum and Andromeda polifolia, the deciduous dwarf shrubs Betula nana and Vaccinium uliginosum, the grass Calamagrostis lapponica and the forb Rubus chamaemorus. 3. We found substantial interspecific differences in leaf nutrient and carbon exchange variables that reflect the response of tundra plants to climate change. S. fuscum had the lowest N and P concentrations, with increasing N and P concentrations (and decreasing C/N and C/P ratios) going from evergreen dwarf shrubs, to the grass, deciduous dwarf shrubs and the forb. Leaf N/P ratios varied between 10 and 14 which points to N-limited plant growth. 4. The natural abundance of ¹⁵N varied very strongly among species and growth forms. These differences corresponded with the presence and type of mycorrhizal association in the plant roots. Leaf carbon isotope discrimination also differed strongly among species and growth forms, but the absolute differences were relatively small (< 5%o). The rank order was: forb and graminoid < moss and evergreen shrubs < deciduous shrubs. 5. After 4 years, the effects of realistic climate change manipulations on leaf nutrient and carbon exchange variables were idiosyncratic with respect to species and generally small compared to the differences among species and growth forms. At the phenotypic level, spring warming or winter snow addition effects occurred as frequently as summer warming effects. 6. This implies that the changes in the species composition and structure of plant communities that have been observed in medium-term warming studies in cold biomes will have much more impact on plant-mediated nutrient and carbon cycling pathways and rates than climate-change induced phenotypic responses, irrespective of the seasonal timing of these climate changes.